Degradable sewage flocculant and preparation method thereof

By introducing multifunctional groups on the surface of chitosan, a degradable wastewater flocculant was prepared, which solved the problem of removing heavy metals and microorganisms in the prior art, achieved efficient flocculation and bactericidal effects, and had recyclable and environmentally friendly characteristic.

CN119160995APending Publication Date: 2024-12-20LIAONING LIAOHE JINYU ENERGY GROUP CO LTD SCIENTIFIC RESEARCH BRANCH
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411454226.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

In the prior art, a single bioflocculant cannot effectively remove heavy metal ions and pathogenic microorganisms, and the commonly used polymer flocculant cannot degrade, resulting in secondary contamination, and the flocculation effect and bactericidal effect are not strong.

Method used

By introducing multifunctional chelating heavy metal ion groups and quaternary ammonium groups on the surface of chitosan, a degradable wastewater flocculant is prepared, using the mesh structure of chitosan and alkenylthiourea cysteine The adsorption properties of monomers, combined with the bridge action of quaternary ammonium salts, achieve flocculation and bactericidal effects.

Benefits of technology

The flocculant has efficient flocculation and bactericidal effects, fast settlement speed, and can be recycled, avoiding the problem of non-degradable chemically synthesized polymer flocculant and has environmentally friendly characteristics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005090000600000051
    Figure BDA0005090000600000051
  • Figure BDA0005090000600000052
    Figure BDA0005090000600000052
  • Figure BDA0005090000600000091
    Figure BDA0005090000600000091
Patent Text Reader

Abstract

The invention relates to the technical field of flocculants, and discloses a flocculant capable of degrading sewage and a preparation method of the flocculant, thiourea, sulfydryl and other groups in an alkenyl thiourea cysteine monomer have excellent adsorption and chelation effects on heavy metal ions, and stable complexes and chelate precipitates can be formed, so that heavy metals are removed from wastewater; sulfydryl and carboxyl in the structure are easily soluble in water, so that the solubility of chitosan is improved, and the coordination capability is improved; the positively charged quaternary ammonium salt cations in the flocculant can adsorb more kaolin particles and neutralize charges on the surfaces of the particles to generate an adsorption bridging effect, and can influence substance energy exchange and normal metabolism of bacterial cell membranes at the same time, so that bacteria are inhibited or killed, and a sterilization effect is achieved; the prepared flocculant still has a good flocculation effect on heavy metal ions after being desorbed and recycled for multiple times, can be recycled, and is non-toxic, harmless and biodegradable.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of flocculants, in particular to a degradable sewage flocculant and a preparation method thereof. Background Art

[0002] In recent years, with the development of metallurgy, papermaking, electroplating, mining and other technologies, a large amount of industrial wastewater including metal ions such as Pb, Cd, Hg, Cr, Cu, Zn, Ni, etc. has been generated. Heavy metal elements are highly toxic and cannot be decomposed. They are carcinogenic, teratogenic, mutagenic and other hazards, posing a threat to human society and the ecological environment. In addition, the discharge standards for heavy metal wastewater are becoming more and more stringent. How to effectively control water pollution caused by heavy metals and try to recycle valuable metals has become an urgent problem to be solved; although conventional technologies such as reverse osmosis, ion exchange, chemical precipitation, solvent extraction and other methods can effectively treat heavy metal wastewater, most methods still produce secondary waste; flocculation method has the characteristics of simplicity and high efficiency, which provides broad prospects for sewage treatment. Therefore, studying and preparing a safe and harmless flocculant is one of the effective ways to improve the quality of water environment.

[0003] Flocculants refer to agents that can destabilize and aggregate various solutes, suspended particles or colloids in aqueous solutions to form flocs, thereby accelerating their sedimentation and ultimately achieving solid-liquid separation. In the prior art, commonly used flocculants mainly include inorganic flocculants and polymer flocculants. Inorganic flocculants include inorganic salt small molecule flocculants and inorganic salt polymer flocculants, which have the advantages of low price and simple and easy use. However, the flocs produced are loose, easy to break, have a low sedimentation rate, and metal ions are easy to form residues in water. Artificially synthesized polymer flocculants, such as polyacrylamide derivatives, polyethyleneimine, polyethylene pyrimidine, etc., are not easily degraded in nature and are prone to secondary pollution. Natural organic flocculants such as chitosan have a long chain structure and are rich in primary amine groups on the main chain of the molecule. They are poorly water-soluble in neutral and alkaline media and have inactive chemical properties, resulting in poor flocculation effects.

[0004] The single biological flocculant in the prior art cannot be recycled, and it is difficult to filter after adsorption, and some of it will dissolve in water. In addition, there are some pathogenic microorganisms or some algae in the sewage that reproduce in large quantities, which deteriorates the water quality. Therefore, it is necessary not only to control the discharge of heavy metal ions in sewage, but also to control the growth and reproduction of harmful microorganisms. At present, some natural polymer compounds themselves have weak flocculation and bactericidal effects, and most of the developed natural polymer water treatment agents are only improved in one aspect. There are relatively few studies on water treatment agents with both high-efficiency flocculation and bactericidal functions. Therefore, the present invention introduces multifunctional chelated heavy metal ion groups and quaternary ammonium salt groups with bactericidal and flocculating bactericidal effects on the surface of chitosan to prepare a flocculating, bactericidal and degradable water treatment agent. Summary of the invention

[0005] The purpose of the present invention is to solve the problems existing in the above-mentioned prior art and to provide a degradable sewage flocculant and a preparation method thereof, which avoids the problem that traditional chemical synthetic polymer flocculants are non-degradable, has good flocculation effect, fast sedimentation rate, and has a certain bactericidal effect. The production process is simple, the cost is low and it can be recycled.

[0006] The present invention is achieved through the following technical solutions:

[0007] A method for preparing a degradable sewage flocculant comprises the following steps: adding chitosan and acetic acid with a mass fraction of 0.5-2% to a reaction flask under a nitrogen atmosphere, stirring and dissolving, adding acrylamide and a structural formula The alkenylthiourea cysteine ​​monomer is stirred and dispersed evenly, an initiator is added and the mouth of the reaction bottle is immediately sealed, and it is placed in a UV light initiation device. The polymerization reaction is carried out at a temperature of 45-60°C for 1-3 hours, and it is naturally cooled to room temperature. It is precipitated with ethanol, filtered and washed with deionized water, and dried in an oven at 50-60°C for 12-24 hours to obtain a degradable sewage flocculant.

[0008] Furthermore, the initiator is any one of 2,2'-azobis[2-(2-imidazolin-2-yl)propane] dihydrochloride, 2,2'-azobisisobutylamidine dihydrochloride or 4,4'-azobis(4-cyanovaleric acid).

[0009] Furthermore, the ratio of chitosan, acrylamide, alkenylthiourea cysteine ​​monomer, and initiator is 100 g: (20-35) g: (2-10) g: (3-5) g.

[0010] Furthermore, the power of the UV light initiator is 450-550W, and the average light intensity is 1100-1300μW / cm 2 .

[0011] Further, the preparation method of alkenylthiourea cysteine ​​monomer comprises the following steps:

[0012] Step (1), under a nitrogen atmosphere, add L-cysteine ​​and dichloromethane to a reaction flask, stir evenly, add triethylamine and 4-chlorophenylisothiocyanate, stir to react, and after the reaction is completed, concentrate under reduced pressure, and purify by column chromatography to obtain chlorophenylthiourea-cysteine ​​monomer.

[0013] Step (2), under a nitrogen atmosphere, add chlorophenylthiourea-cysteine ​​monomer and N,N-dimethylformamide to a reaction flask, stir evenly, add N-[(3-(dimethylamino)propyl]methacrylamide, stir to react, and after the reaction is completed, cool to room temperature, filter, and wash with deionized water to obtain an olefinthiourea cysteine ​​monomer.

[0014] Furthermore, in step (1), the ratio of L-cysteine, triethylamine and 4-chlorophenylisothiocyanate is 1 mol:(3-3.5) mol:(1.05-1.2) mol.

[0015] Furthermore, in step (1), the reaction temperature is 20-35° C. and the reaction time is 16-32 h.

[0016] Furthermore, in step (2), the ratio of chlorophenylthiourea-cysteine ​​monomer to N-[(3-(dimethylamino)propyl]methacrylamide is 1 mol:(1.02-1.1) mol.

[0017] Furthermore, in step (2), the reaction temperature is 90-110° C. and the reaction time is 12-24 h.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] Chitosan itself has a large specific surface area, and its molecular chain stretches into a network structure, which can sweep up particles and suspended matter in sewage like a "net". The large number of hydroxyl groups in its structure have a chelating effect on heavy metal ions. At the same time, the introduced polyacrylamide structure increases the relative molecular mass of chitosan, which is beneficial to enhance the adsorption performance; the thiourea, thiol and other groups in the alkenylthiourea cysteine ​​monomer have excellent adsorption and chelating effects on heavy metal ions, forming stable complexes and chelate precipitations, thereby removing heavy metals from wastewater; the thiol and carboxyl groups in its structure are easily soluble in water, which improves the solubility of chitosan and enhances its coordination capacity; quaternary ammonium salt cations can connect heavy metal ions through adsorption bridging to form larger flocs; the synergistic effect of chitosan and polyacrylamide provides a strong adsorption bridging effect, improves the sedimentation of flocs, and further improves the efficiency of flocculants in removing heavy metals; after multiple desorption and recovery, it still has a good flocculation effect on heavy metal ions and can be recycled.

[0020] The positively charged quaternary ammonium salt cations in the flocculant can adsorb more kaolin particles, neutralize the charge on the surface of the particles, reduce or eliminate the electrostatic repulsion between the particles, and produce an adsorption bridging effect to combine the kaolin particles together. The aggregation of the particles makes the volume reach a certain level, forming flocs that disperse from the water; at the same time, the positively charged quaternary ammonium salt cationic groups can selectively adsorb to Escherichia coli, causing the bacterial surface to be covered by cationic groups, affecting the material energy exchange and normal metabolism of the cell membrane, thereby inhibiting or killing the bacteria and playing a bactericidal role.

[0021] Chitosan is an environmentally friendly, natural, non-toxic material with good adsorption and flocculation effects on heavy metal ions. The degradable flocculant obtained by the present invention has a better adsorption effect on heavy metal ions and reduces the generation of secondary pollutants during the adsorption process. It also has the advantages of being non-toxic, biodegradable, low-cost, and recyclable. DETAILED DESCRIPTION

[0022] In order to further understand the present invention, the technical solution of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0023] Unless otherwise specified, the raw materials and reagents used in this application are commercially available or can be prepared by known methods.

[0024] L-Cysteine, CAS number is 52-90-4.

[0025] 4-Chlorophenylisothiocyanate, CAS number is 2131-55-7.

[0026] N-[(3-(Dimethylamino)propyl]methacrylamide, CAS number is 5205-93-6.

[0027] 2,2'-Azobis[2-(2-imidazolin-2-yl)propane] dihydrochloride, CAS number is 27776-21-2.

[0028] 2,2'-Azobisisobutylamidine dihydrochloride, CAS number is 2997-92-4.

[0029] 4,4'-Azobis(4-cyanovaleric acid), CAS number is 2638-94-0.

[0030] Example 1

[0031] (1) Under nitrogen atmosphere, 125 mmol of L-cysteine ​​and 750 mL of dichloromethane were added to a reaction flask, and after stirring, 400 mmol of triethylamine and 137.5 mmol of 4-chlorophenylisothiocyanate were added, and the mixture was reacted at 25° C. for 24 h, concentrated under reduced pressure, and purified by column chromatography (ethyl acetate and petroleum ether 1:3) to obtain chlorophenylthiourea-cysteine ​​monomer. The preparation reaction formula is as follows:

[0032]

[0033] (2) Under nitrogen atmosphere, 110 mmol of chlorophenylthiourea-cysteine ​​monomer and 1320 mL of N,N-dimethylformamide were added to the reaction flask, and after stirring, 115.5 mmol of N-[(3-(dimethylamino)propyl]methacrylamide was added, and the mixture was reacted at 100° C. for 16 h. The mixture was cooled to room temperature, filtered, and washed with deionized water to obtain alkenylthiourea cysteine ​​monomer. The preparation reaction formula is as follows:

[0034]

[0035] (3) Under nitrogen atmosphere, 100 g of chitosan and 1.5% acetic acid were added to the reaction flask. After stirring and dissolving, 25 g of acrylamide and 2 g of ethylenethiourea cysteine ​​monomer were added. Stirring was continued until uniform dispersion was achieved. 4 g of initiator 2,2'-azobis[2-(2-imidazoline-2-yl)propane] dihydrochloride was added and the mouth of the reaction flask was immediately sealed. The flask was placed in an ultraviolet light initiation device with a power of 500 W and an average light intensity of 1200 μW / cm 2 The polymerization reaction was carried out at a temperature of 55°C for 2 hours, naturally cooled to room temperature, precipitated with ethanol, filtered and washed with deionized water, and dried in an oven at 55°C for 16 hours to obtain a degradable sewage flocculant.

[0036] Example 2

[0037] (1) Under nitrogen atmosphere, 220 mmol of L-cysteine ​​and 1100 mL of dichloromethane were added to a reaction flask, and after stirring, 660 mmol of triethylamine and 231 mmol of 4-chlorophenylisothiocyanate were added, and the mixture was reacted at 35° C. for 16 h, concentrated under reduced pressure, and purified by column chromatography (ethyl acetate and petroleum ether 1:3) to obtain chlorophenylthiourea-cysteine ​​monomer.

[0038] (2) Under nitrogen atmosphere, 180 mmol of chlorophenylthiourea-cysteine ​​monomer and 1440 mL of N,N-dimethylformamide were added to a reaction flask, and after stirring, 183.6 mmol of N-[(3-(dimethylamino)propyl]methacrylamide was added, and the mixture was reacted at 110° C. for 12 h. The mixture was cooled to room temperature, filtered, and washed with deionized water to obtain an olefinthiourea cysteine ​​monomer.

[0039] (3) Under nitrogen atmosphere, 100 g of chitosan and 0.5% acetic acid were added to the reaction flask. After stirring and dissolving, 20 g of acrylamide and 4 g of ethylenethiourea cysteine ​​monomer were added. Stirring was continued until uniform dispersion was achieved. 3 g of initiator 2,2'-azobisisobutylamidine dihydrochloride was added and the mouth of the reaction flask was immediately sealed. The flask was placed in an ultraviolet light initiation device with a power of 550 W and an average light intensity of 1300 μW / cm 2 The polymerization reaction was carried out at a temperature of 60°C for 1 hour, naturally cooled to room temperature, precipitated with ethanol, filtered and washed with deionized water, and dried in an oven at 60°C for 12 hours to obtain a degradable sewage flocculant.

[0040] Example 3

[0041] (1) Under nitrogen atmosphere, 40 mmol of L-cysteine ​​and 400 mL of dichloromethane were added to a reaction flask. After stirring, 140 mmol of triethylamine and 482 mmol of 4-chlorophenylisothiocyanate were added. The mixture was reacted at 20° C. for 32 h, concentrated under reduced pressure, and purified by column chromatography (ethyl acetate and petroleum ether 1:3) to obtain chlorophenylthiourea-cysteine ​​monomer.

[0042] (2) Under nitrogen atmosphere, 32 mmol of chlorophenylthiourea-cysteine ​​monomer and 480 mL of N,N-dimethylformamide were added to a reaction flask, and after stirring, 35.2 mmol of N-[(3-(dimethylamino)propyl]methacrylamide was added, and the mixture was reacted at 90° C. for 24 h. The mixture was cooled to room temperature, filtered, and washed with deionized water to obtain an olefinthiourea cysteine ​​monomer.

[0043] (3) Under nitrogen atmosphere, 100 g of chitosan and 2% acetic acid were added to the reaction flask. After stirring and dissolving, 35 g of acrylamide and 6 g of ethylenethiourea cysteine ​​monomer were added. Stirring was continued until uniform dispersion was achieved. 5 g of initiator 4,4'-azobis(4-cyanovaleric acid) was added and the mouth of the reaction flask was immediately sealed. The flask was placed in an ultraviolet light initiation device with a power of 450 W and an average light intensity of 1100 μW / cm 2 The polymerization reaction was carried out at a temperature of 45°C for 3 hours, naturally cooled to room temperature, precipitated with ethanol, filtered and washed with deionized water, and dried in an oven at 50°C for 24 hours to obtain a degradable sewage flocculant.

[0044] Example 4

[0045] (1) Under nitrogen atmosphere, 80 mmol of L-cysteine ​​and 520 mL of dichloromethane were added to a reaction flask. After stirring, 260 mmol of triethylamine and 92 mmol of 4-chlorophenylisothiocyanate were added. The mixture was reacted at 30° C. for 24 h, concentrated under reduced pressure, and purified by column chromatography (ethyl acetate and petroleum ether 1:3) to obtain chlorophenylthiourea-cysteine ​​monomer.

[0046] (2) Under nitrogen atmosphere, 65 mmol of chlorophenylthiourea-cysteine ​​monomer and 780 mL of N,N-dimethylformamide were added to a reaction flask, and after stirring, 68.9 mmol of N-[(3-(dimethylamino)propyl]methacrylamide was added, and the mixture was reacted at 105° C. for 15 h. The mixture was cooled to room temperature, filtered, and washed with deionized water to obtain an olefinthiourea cysteine ​​monomer.

[0047] (3) Under nitrogen atmosphere, 100 g of chitosan and 1% acetic acid were added to the reaction flask. After stirring and dissolving, 30 g of acrylamide and 8 g of ethylenethiourea cysteine ​​monomer were added. Stirring was continued until uniform dispersion was achieved. 3.5 g of initiator 2,2'-azobis[2-(2-imidazolin-2-yl)propane] dihydrochloride was added and the mouth of the reaction flask was immediately sealed. The flask was placed in an ultraviolet light initiation device. The power of the ultraviolet light initiation device was 480 W and the average light intensity was 1250 μW / cm 2 The polymerization reaction was carried out at a temperature of 55°C for 2 hours, naturally cooled to room temperature, precipitated with ethanol, filtered and washed with deionized water, and dried in an oven at 60°C for 24 hours to obtain a degradable sewage flocculant.

[0048] Example 5

[0049] (1) Under nitrogen atmosphere, 25 mmol of L-cysteine ​​and 220 mL of dichloromethane were added to a reaction flask. After stirring, 80 mmol of triethylamine and 29 mmol of 4-chlorophenylisothiocyanate were added. The mixture was reacted at 35° C. for 32 h, concentrated under reduced pressure, and purified by column chromatography (ethyl acetate and petroleum ether 1:3) to obtain chlorophenylthiourea-cysteine ​​monomer.

[0050] (2) Under nitrogen atmosphere, 20 mmol of chlorophenylthiourea-cysteine ​​monomer and 270 mL of N,N-dimethylformamide were added to a reaction flask, and after stirring, 21 mmol of N-[(3-(dimethylamino)propyl]methacrylamide was added, and the mixture was reacted at 95° C. for 24 h. The mixture was cooled to room temperature, filtered, and washed with deionized water to obtain an olefinthiourea cysteine ​​monomer.

[0051] (3) Under nitrogen atmosphere, 100 g of chitosan and 2% acetic acid were added to the reaction flask. After stirring and dissolving, 30 g of acrylamide and 10 g of ethylenethiourea cysteine ​​monomer were added. Stirring was continued until uniform dispersion was achieved. 5 g of initiator 2,2'-azobisisobutylamidine dihydrochloride was added and the mouth of the reaction flask was immediately sealed. The flask was placed in an ultraviolet light initiation device with a power of 520 W and an average light intensity of 1300 μW / cm 2 The polymerization reaction was carried out at a temperature of 55°C for 2 hours, naturally cooled to room temperature, precipitated with ethanol, filtered and washed with deionized water, and dried in an oven at 60°C for 18 hours to obtain a degradable sewage flocculant.

[0052] Comparative Example 1

[0053] Under nitrogen atmosphere, 100 g of chitosan and 1.5% acetic acid were added to the reaction flask, stirred and dissolved, and then 25 g of acrylamide and 2 g of (3-methacrylamidepropyl)trimethylammonium chloride (CAS No. 51410-72-1, structural formula: ), continue to stir and disperse evenly, add 4g of initiator 2,2'-azobis[2-(2-imidazoline-2-yl)propane] dihydrochloride and immediately seal the mouth of the reaction bottle, and place it in an ultraviolet light initiation device with a power of 500W and an average light intensity of 1200μW / cm 2 The polymerization reaction was carried out at a temperature of 55°C for 2 hours, naturally cooled to room temperature, precipitated with ethanol, filtered and washed with deionized water, and dried in an oven at 55°C for 16 hours to obtain a sewage flocculant.

[0054] Comparative Example 2

[0055] Under nitrogen atmosphere, add 100g chitosan and 1.5% acetic acid to the reaction flask, stir and dissolve, add 25g acrylamide, continue to stir and disperse evenly, add 4g initiator 2,2'-azobis[2-(2-imidazoline-2-yl)propane] dihydrochloride and immediately seal the mouth of the reaction bottle, and place it in an ultraviolet light initiator device with a power of 500W and an average light intensity of 1200μW / cm 2 The polymerization reaction was carried out at a temperature of 55°C for 2 hours, naturally cooled to room temperature, precipitated with ethanol, filtered and washed with deionized water, and dried in an oven at 55°C for 16 hours to obtain a sewage flocculant.

[0056] Flocculation experiment: Use distilled water to prepare a metal ion solution with a concentration of 0.005 mol / L (Pb 2+ , Cu 2+ , Hg 2+ 、Cd 2+ 、Ni 2+), take 50mL of metal ion solution and place it in a 100mL stoppered conical flask, add 0.05g of the prepared sewage flocculant dropwise with a syringe, stir at 25℃ and 200r / min for 30min and filter, test the concentration of heavy metal ions before and after adsorption in the filtrate, and use EDTA complexometric titration to determine Hg 2+ , Flame Atomic Absorption Spectrophotometry for the Determination of Pb 2+ , Cu 2+ 、Cd 2+ 、Ni 2+ ; Removal rate R (%) = (C0-C1) / C0×100%; where C0 and C1 are the concentrations of heavy metal ions in the solution before and after adsorption (mol / L), respectively.

[0057] Table 1 Removal rate of heavy metal ions (%)

[0058]

[0059] From the test results in the table above, it can be seen that with the increase of the content of alkenylthiourea cysteine ​​monomer, the adsorption capacity of sewage flocculants for heavy metals gradually increases, indicating that Pb 2+ , Cu 2+ , Hg 2+ 、Cd 2+ 、Ni 2+ Under the action of flocculants, these heavy metal ions can bridge to form coarse flocs, which is beneficial to sedimentation and separation; this is because, on the one hand, chitosan itself has a large specific surface area, and the molecular chain stretches into a network structure, which can sweep up particles and suspended matter in sewage like a "net". The large number of hydroxyl groups in its structure have a chelating effect on heavy metal ions. At the same time, the introduced polyacrylamide structure increases the relative molecular mass of chitosan, which is beneficial to enhance the adsorption performance; on the other hand, the thiourea, thiol and other groups in the alkenylthiourea cysteine ​​monomer have excellent adsorption and chelation effects on heavy metal ions, and can form stable complexes and chelate precipitations, thereby removing heavy metals from wastewater; the thiol and carboxyl groups in its structure are easily soluble in water, which improves the solubility of chitosan and enhances its coordination capacity; quaternary ammonium salt cations can connect heavy metal ions by adsorption bridging to form larger flocs; chitosan and polyacrylamide structures produce a synergistic effect, providing a strong adsorption bridging effect and improving the sedimentation of flocs, further improving the efficiency of flocculants in removing heavy metals.

[0060] Comparative Example 1 does not contain thiourea, thiol and other groups, and has limited chelating effect on heavy metals, but contains quaternary ammonium cations and has a certain adsorption effect; Comparative Example 2 does not contain chelating groups such as N and S, nor does it contain quaternary ammonium cations, so it has the worst removal effect on heavy metals.

[0061] Adsorption regeneration performance test: 1 mol / L hydrochloric acid was used as the desorbent, and 1 g of the adsorbed Pb in Example 4 was taken. 2+ , Cu 2+ , Hg 2+ 、Cd 2+ 、Ni 2+ The flocculant is desorbed. After the desorption is completed, the flocculant is recovered and the adsorption-desorption is repeated 3 times. The removal rate of heavy metal ions by the flocculant after each desorption is measured.

[0062] Table 2 Adsorption regeneration performance test of flocculants

[0063]

[0064] It can be seen from the test results in the above table that the flocculant prepared by the present invention still has a good flocculation effect on heavy metal ions after desorption and recovery, and can be recycled.

[0065] Flocculation performance test: In a 2L beaker, add 5g kaolin and 1L water, adjust the pH of the system to 6 with 1mol / L sulfuric acid solution, stir evenly, use a turbidity meter to test the initial turbidity T0 of the kaolin solution, then add 0.05g of the prepared flocculant, stir at 25℃ and 200r / min for 10min, then reduce to 30r / min and slowly stir for 15min, test the turbidity T1 of the kaolin solution after flocculation, and calculate the kaolin removal rate R=(T0-T1) / T0×100%.

[0066] Table 3 Test on the removal rate of kaolin

[0067] Kaolin removal rate (%) Example 1 86.1 Example 2 90.2 Example 3 95.6 Example 4 98.1 Example 5 98.5 Comparative Example 1 85.8 Comparative Example 2 40.1

[0068] It can be seen from the test results in the above table that with the increase of the content of alkenylthiourea cysteine ​​monomer, the removal ability of the sewage flocculant for kaolin solution is gradually enhanced, wherein the removal rate in Example 4 reaches 98.1%. This is because the kaolin solution exists in the form of negatively charged particles, and the chelating adsorption effect is not obvious; therefore, under the system of pH=6, the positively charged quaternary ammonium salt cations in the flocculant can adsorb more kaolin particles, neutralize the charge on the surface of the particles, reduce or eliminate the electrostatic repulsion between the particles, generate an adsorption bridging effect to combine the kaolin particles together, and the aggregation of the particles makes the volume reach a certain level, forming flocs that are dispersed from the water.

[0069] Sterilization performance test: Weigh 25g of LB agar medium and dissolve it in 1L of distilled water. Use 0.1mol / L sodium hydroxide solution to adjust the pH of the medium solution to 7.0. Then place the medium solution in an autoclave at 121℃ for 15min and shake culture at 37℃ for 24h to obtain E. coli mother solution. Centrifuge to remove the upper culture medium, take out the E. coli cell precipitate, add appropriate amount of pure water and stir thoroughly to disperse the cells to obtain a density of 1.0×10 7 CFU / mL of Escherichia coli suspension; take 100mL of Escherichia coli suspension, add 1g of flocculant, stir evenly, use a syringe to extract the supernatant 1cm below the liquid surface, and use a turbidity meter to test the residual turbidity value of the supernatant.

[0070] Table 4 Bactericidal performance test

[0071] Residual turbidity value (NTU) Example 1 48 Example 2 35 Example 3 23 Example 4 15 Example 5 12 Comparative Example 1 49 Comparative Example 2 82

[0072] Escherichia coli is a representative bacterium of the genus Escherichia. Usually, pathogenic Escherichia coli can be spread among people through physical objects, drinking water and other channels, causing intestinal infections, diarrhea, vomiting, cholecystitis and other diseases. Therefore, the number of Escherichia coli in water bodies needs to be controlled within a certain range; the smaller the residual turbidity value, the more effectively the pathogenic Escherichia coli in the water is removed, and the better the water quality; from the test data in the above table, it can be seen that the positively charged quaternary ammonium salt cationic groups in the flocculant can selectively adsorb to Escherichia coli, causing the bacterial surface to be covered by cationic groups, affecting the material energy exchange and normal metabolism of the cell membrane, thereby inhibiting or killing the bacteria and playing a bactericidal role.

[0073] The present application is described in detail above in conjunction with specific implementation methods and exemplary examples, but these descriptions cannot be understood as limitations of the present application. Those skilled in the art understand that, without departing from the spirit and scope of the present application, a variety of equivalent replacements, modifications or improvements can be made to the technical solutions and implementation methods of the present application, all of which fall within the scope of the present application. The scope of protection of the present application shall be subject to the attached claims.

Claims

1. A method for preparing a degradable sewage flocculant, characterized in that: The preparation method comprises the following steps: adding chitosan and acetic acid with a mass fraction of 0.5-2% to a reaction flask under a nitrogen atmosphere, stirring and dissolving, adding acrylamide and a structural formula The alkenylthiourea cysteine ​​monomer is stirred and dispersed evenly, an initiator is added and the mouth of the reaction bottle is immediately sealed, and it is placed in a UV light initiation device. The polymerization reaction is carried out at a temperature of 45-60°C for 1-3 hours, and it is naturally cooled to room temperature. It is precipitated with ethanol, filtered and washed with deionized water, and dried in an oven at 50-60°C for 12-24 hours to obtain a degradable sewage flocculant.

2. The method for preparing a degradable sewage flocculant according to claim 1, characterized in that: The initiator is any one of 2,2'-azobis[2-(2-imidazolin-2-yl)propane]dihydrochloride, 2,2'-azobisisobutylamidinedihydrochloride or 4,4'-azobis(4-cyanovaleric acid).

3. The method for preparing a degradable sewage flocculant according to claim 1, characterized in that: The ratio of chitosan, acrylamide, alkenylthiourea cysteine ​​monomer and initiator is 100g:(20-35)g:(2-10)g:(3-5)g.

4. The method for preparing a degradable sewage flocculant according to claim 1, characterized in that: The power of the ultraviolet light initiation device is 450-550W, and the average light intensity is 1100-1300μW / cm 2 .

5. The method for preparing a degradable sewage flocculant according to claim 1, characterized in that: The preparation method of the alkenylthiourea cysteine ​​monomer comprises the following steps: Step (1), under a nitrogen atmosphere, add L-cysteine ​​and dichloromethane to a reaction flask, stir evenly, add triethylamine and 4-phenylchloroisothiocyanate, stir to react, and after the reaction is completed, concentrate under reduced pressure, and purify by column chromatography to obtain chlorophenylthiourea-cysteine ​​monomer; Step (2), under a nitrogen atmosphere, add chlorophenylthiourea-cysteine ​​monomer and N,N-dimethylformamide to a reaction flask, stir evenly, add N-[(3-(dimethylamino)propyl]methacrylamide, stir to react, and after the reaction is completed, cool to room temperature, filter, and wash with deionized water to obtain an olefinthiourea cysteine ​​monomer.

6. The method for preparing a degradable sewage flocculant according to claim 5, characterized in that: In the step (1), the ratio of L-cysteine, triethylamine and 4-phenylchloroisothiocyanate is 1 mol: (3-3.5) mol: (1.05-1.2) mol.

7. The method for preparing a degradable sewage flocculant according to claim 5, characterized in that: In the step (1), the reaction temperature is 20-35° C. and the reaction time is 16-32 h.

8. The method for preparing a degradable sewage flocculant according to claim 5, characterized in that: In the step (2), the ratio of chlorophenylthiourea-cysteine ​​monomer to N-[(3-(dimethylamino)propyl]methacrylamide is 1 mol:(1.02-1.1) mol.

9. The method for preparing a degradable sewage flocculant according to claim 5, characterized in that: In the step (2), the reaction temperature is 90-110° C. and the reaction time is 12-24 h.

10. A degradable sewage flocculant, characterized in that: Obtained by the preparation method according to any one of claims 1 to 9.

Citation Information

Cited By

  • Activated carbon-based adsorbent for heavy metal ions and preparation method of activated carbon-based adsorbent

    CN119633753A

  • Flocculating agent composition for petroleum refining sewage and preparation method thereof

    CN120646992A